The Immune and Inflammatory Basis of Acquired Pediatric Cardiac Disease - Jui, Elysa; Singampalli, Kavya L.; Shani, Kevin; Ning, Yao; Connell, Jennifer P.; Birla, Ravi K.; Bollyky, Paul L.; Caldarone, Christopher A.; Keswani, Sundeep G.; Grande-Allen, K. Jane (Frontiers in Cardiovascular Medicine, 2021)
Children with acquired heart disease face significant health challenges, including a lifetime of strict medical management, multiple cardiac surgeries, and a high mortality risk. Though the presentation of these conditions is diverse, a unifying factor is the role of immune and inflammatory responses in their development and/or progression. For example, infectious agents have been linked to pediatric cardiovascular disease, leading to a large health burden that disproportionately affects low-income areas. Other implicated mechanisms include antibody targeting of cardiac proteins, infection of cardiac cells, and inflammation-mediated damage to cardiac structures. These changes can alter blood flow patterns, change extracellular matrix composition, and induce cardiac remodeling. Therefore, understanding the relationship between the immune system and cardiovascular disease can inform targeted diagnostic and treatment approaches. In this review, we discuss the current understanding of pediatric immune-associated cardiac diseases, challenges in the field, and areas of research with potential for clinical benefit.